Agreement And Homologation Commissions As An Implementation ‎‎mechanisms Of ‎reforms Of Algerian Educational System ‏- ‏‎-a Study In The Legislative Framework And The Difficulties Of ‎activation - Benyettou, oussama (The journal of Teacher Researcher of Legal and political Studies, 2024)
This study aims to highlight the role of those commissions by highlighting ‎‎and analyzing their legislative ‎framework, and analyzing the difficulties of ‎activating ‎of their role, as they are two mechanisms ‎developed by Ministry of Education, ‎to ‎implement educational reforms, especially the reform of ‎education ‎curricula and ‎programmes, which ‎require, the form and content of pedagogical means and pillars, ‎which, before being distributed to educational and educational institutions, ‎requires an official body that guarantees ‎the integrity of its selection ‎and quality.‎ Keywords: Agreement ; Homologation ; Commission ; Educational System ; Algeria.‎